2013
DOI: 10.4238/2013.november.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of novel single-nucleotide polymorphisms of the vascular endothelial growth factor-A gene with high-altitude adaptation in yak (Bos grunniens)

Abstract: ABSTRACT. Vascular endothelial growth factor-A gene (VEGF-A) is a key regulator of angiogenesis and an endothelial cell mitogen that plays an important role in high-altitude adaptation. In this study, we detected 2 novel single-nucleotide polymorphisms (SNPs) of VEGF-A by screening for genetic variation in 700 individuals of 3 domestic Chinese yak breeds -namely Gannan (GN), Datong (DT), and Tianzhu white (TZW) -using polymerase chain reaction-restriction fragment length polymorphism and DNA sequencing techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The result was on expected line as it is a known fact that during hypoxic condition, VEGF‐A is essential for the growth of new blood vessels. This helps in angiogenesis by recruiting vascular endothelial cells in the hypoxic area (Nagy et al, ; Wu et al, ). Over expression of VEGF in PBMCs of high altitude cattle suggested this gene to be a strong candidate gene for high altitude adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…The result was on expected line as it is a known fact that during hypoxic condition, VEGF‐A is essential for the growth of new blood vessels. This helps in angiogenesis by recruiting vascular endothelial cells in the hypoxic area (Nagy et al, ; Wu et al, ). Over expression of VEGF in PBMCs of high altitude cattle suggested this gene to be a strong candidate gene for high altitude adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Tibetan Sheep has been living in plateaus at high altitudes with low oxygen and high radiation levels for a long time; these differences in their living environments have a substantial influence on their physiology and organ structure (Wu et al., 2013; Shi et al., 2018). This study showed that the basic structures of testicular and epididymal arteries and microarteries in Tibetan Sheep were similar to those in other mammals (Polguj et al., 2011; Polguj et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that plateau animals such as Tibetan Sheep and Yak localized at high altitudes, after a long term of natural selection of their morphology, skin, physiology and biochemical indicators, showed good adaptability to high altitude hypoxia (Wang et al., 2013; Wu et al., 2013). The studies showed that the plateau condition has a certain effect on the reproductive success of the animals (Liao et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SNP rs2381 A→G was specific to yak, cattle were homozygous with G allele at the same locus (Figure A2, B2). The significant difference among the four populations may be caused by the differences in the breeds, but the significant differences (p<0.05) in allele or genotype frequencies of SNP rs2381 A→G in PL yak (high altitude) and GN, DT yak (middle-altitude), TZ yak (low-altitude) (p<0.05), which have lived at high altitude for many generations, is likely the result of a long period of natural selection for environmental adaptation [33]. However, no significant difference in allele or genotype frequencies of SNP rs4331 C→G among in 4 yak breeds (p>0.05), and we suspect that the differentiation between high-altitude and low-altitude yaks is relatively young because some mutations with relevance to high-altitude adaptation are not spread completely throughout the yak population.…”
Section: Discussionmentioning
confidence: 99%